Functional gastrointestinal disorders in newborns: nutritional perspectives - Roberto Bellù; Manuela Condò (PAGEPress Publications, 2018)
Functional gastrointestinal disorders (FGIDs) definition in children has changed over the years trying to facilitate clinicians, because the diagnostic process is complicated by the interpretation variability of symptoms described by children or by their caregivers for newborns and toddlers. This review refers to the Rome IV classification system, drafted in 2016. FGIDs pathophysiology is multifactorial and still poor understood, with limitations for the therapeutic process, which results often in unnecessary and alternative treatments trying to reduce the relevant caregiver distress, but with increased costs for families and for the National Health Service. This study reports the most recent evidence-based treatments for FGIDs in newborns: though in most cases the first action is an educational and behavioral intervention, reassuring caregivers about the transient and self-limiting natural history of FGIDs, there is now more evidence to recommend probiotics in some infant FGIDs.